The Role of Family Communication in Transmitting Environmental Values among the Baduy - Saputra, Faisal Tomi; La Ungka, Usman; Karman, Karman; Indriasari, Devi Tri (Jurnal The Messenger, 2025)
Purpose: This study examined how family communication transmitted environmental values among the Baduy (Indonesia), linking their unique traditional ecological knowledge, cultural practices, and identity-based frameworks to sustainability outcomes to inform broader conservation efforts. Methods: This qualitative study conducted in-depth interviews with four purposefully selected Baduy participants (Banten, Indonesia) to capture diverse perspectives. Informants included a ‘Tokoh Adat’ (customary leader), the ‘Kepala Desa Kanekes’ (village head), and two ‘Warga Baduy’ (general community members), representing traditional authority, administrative leadership, and community viewpoints. Findings: Findings illuminate the Baduy people's profound integration of traditional agriculture and environmental preservation. This commitment manifests in their strict chemical prohibition, reliance on natural fertilizers, deep reverence for protected forests, and adherence to eco-friendly farming methods. These practices are embedded within a robust framework of customary law (‘adat’) and significantly informed by ‘Karma’ belief, reflecting a sophisticated understanding of long-term ecological consequences. Furthermore, these ingrained traditions fundamentally shape intergenerational communication, positioning the family as the primary conduit for transmitting vital environmental values and ecological knowledge. This dynamic process actively cultivates environmental responsibility and perpetuates a harmonious coexistence with nature within the community. Originality: Providing novel insights, this qualitative study uniquely examined family communication's role in embedding environmental values across Baduy generations (Indonesia). Findings illuminate how traditional ecological knowledge and cultural practices synergize, driving sustainable agriculture/waste management and reinforcing community resilience through ancestral wisdom, informing culturally grounded conservation.